Analisis Tingkat Kepuasan Pelanggan Perusahaan Air Minum Daerah Lematang Enim Kabupaten Muara Enim - Wahyu Ningsih; Heni Fitriani; Febrian . H (Syntax Corporation, 2023)
Many basic problems cause the level of performance and service in PDAM Lematang Enim to be low such as low water discharge of the Enim River, polluted raw water sources, changing raw water conditions, distribution of water to people's homes that often experience congestion, turbid water and unfit for consumption. From the above problems, this study raises one problem in PDAM Lematang Enim, Muara Enim Regency, namely analyzing customer satisfaction with the services and products provided by PDAM. Previous research on PDAMs was quite widely conducted, but research on the level of customer satisfaction in PDAM Lematang Enim Muara Enim is still limited and has not been done much, so further research is needed to assess how customer ratings of PDAMs will be analyzed and can be a reference for PDAM Lematang Enim performance. The data analysis used in the study consisted of customer satisfaction index (CSI) analysis, and binary logistic regression analysis. CSI analysis was conducted to assess the level of satisfaction of PDAM Lematang Enim Muara Enim service users. The results of the CSI analysis will then be used to determine the factors that affect the level of service user satisfaction using binary logistic regression analysis. The results obtained from this study from 135 respondents who are customers of PDAM Lematang Enim are PDAM Lematang Enim in general has carried out operational activities quite well overall which has been included in the Satisfied category with a CSI value of 67.6075028.